Longitudinal Effects of the Family Support Program Chancenreich on Parental Involvement and the Language Skills of Preschool Children - Cohen, Franziska; Schünke, Juliane; Vogel, Eric; Anders, Yvonne (Frontiers in Psychology, 2020)
When they enter primary school children already vary significantly in their language skills, depending at least in part on their family’s social background. In particular, the home learning environment plays a significant role in children’s development. For that reason, early intervention programs have been developed to obviate learning difficulties and to promote health, children’s development, and educational equality. The family support program Chancenreich aims to encourage the interaction and relationship between parents and children through two different course formats. The present study examines the longitudinal effects of attending the Chancenreich program and different course formats on a) parents attending further educational services for children after completing the program, b) children’s vocabulary and level of grammar development at the age of five and c) the children’s vocabulary development between the ages of three and five. Furthermore, we examine the relationship between family characteristics and the attendance rates of different course formats of the Chancenreich program at the first and second point of measurement. The study follows a longitudinal design with two points of measurements (T1: Mage = 41 months, T2: Mage = 68 months), and a sample size of 121 parents and their children at T2 in the intervention group and 41 parents and their children in the comparison group. Findings indicate that attendance of the Chancenreich program’s courses is related to child and family characteristics and to later patterns of course participation after completing the program. Further, both children’s level of vocabulary skills (PPVT) at the age of five and their development between the ages of three and five benefit from the parental participation in parenting skills training at the age of three. Implications and future research on the effectiveness of family support programs are discussed.